MAGNETIC HYPERTHERMIA OF MICROORGANISMS WITH NATURAL FERRIMAGNETIC PROPERTIES - Gorobets, Svitlana; Gorobets, Oksana; Kuzminykh, Liubov; Shevgalishyn, Roman (Proceedings of National Aviation University (archive), 2019)
Aim and Objectives: Biogenic magnetic nanoparticles of microorganisms are not taken into account when neutralized by their magnetic hyperthermia. The aim is to identify microorganisms, which take into account the characteristics of their own biogenic magnetic nanoparticles can lead to a noticeable increase in the effectiveness of magnetic hyperthermia. Methods: Research the study used methods of comparative genomics, in particular, pair alignment using the Genbank database. The alignment of proteomes of magnetotactic bacteria Magnetospirillum gryphiswaldense MSR-1 with the proteomes of pathogenic microorganisms, which were classified according to the site of localization and the type of internal structure of their biogenic magnetic nanoparticles, was carried out. Results: The genomes of 24 strains of pathogenic microorganisms were analyzed belonging to such genus: Staphylococcus, Pseudomonas, Bacillus, Shigella, Clostridioides, Streptococcus, Peptostreptococcus. It was shown that three of them have crystalline intracellular biogenic magnetic nanoparticles, 11 strains have extracellular crystalline, 8 – intracellular amorphous, 3 – extracellular amorphous. The paper also presents calculations of the dipole-dipole strengths of interactions between the amorphous biogenic nanoparticles of Staphylococcus aureus and artificial magnetic nanoparticles. Discussion: We recommend using methods of comparative genomics for the separation of microorganisms with magnetic properties for the selection of a more effective method of neutralization by magnetic hyperthermia. Thus, 3 strains with crystalline intracellular biogenic magnetic nanoparticles can be neutralized by the magnetic hyperthermia, using their own particles as a magnetic material. Other 21 strains with extracellular crystalline, intracellular amorphous and extracellular amorphous magnetic nanoparticles can be neutralized by magnetic hyperthermia using methods of artificial magnetically labeled. It is shown that the forces of dipole-dipole interactions between amorphous magnetic nanoparticles and artificial magnetic nanoparticles are enough to magnetically labeled of Staphylococcus aureus and further neutralize them using magnetic hyperthermia. Conclusions: The use of the natural ferromagnetic properties of microorganisms will increase the effectiveness of the neutralization of magnetic hyperthermia.